Optimización de las operaciones unitarias de la planta de tratamiento de aguas residuales “Ambato” ubicada en el sector las Viñas en el cantón Ambato - López Olmedo, Dany Diogo (2026)
This research evaluates the operational performance of the Ambato Wastewater Treatment Plant (WWTP) with the aim of analyzing the efficiency of contaminant removal and proposing technical improvements to optimize treatment, especially with regard to nutrient removal. The study was developed using an experimental-analytical approach, structured in phases that included the characterization of the influent and effluent, the individual evaluation of the unit operations, and the proposal for the optimization of the biological system. The characterization of the wastewater was based on spot sampling and the analysis of monthly information for the year 2024, provided by the operating company EP-EMAPA-A. The results show that the WWTP performs adequately in removing organic matter, suspended solids, and pathogenic microorganisms, as reflected in high BOD₅, COD, and turbidity efficiencies, as well as effective disinfection. However, limitations were identified in the removal of total Kjeldahl nitrogen and total phosphorus, with values that in certain periods exceed the limits established in current environmental regulations. The analysis of the unit operations made it possible to determine that these deficiencies are associated with the configuration of the biological reactor, which operates only under aerobic conditions, without stages that allow denitrification. Based on these results, a technical redesign of the biological system was developed, considering the incorporation of an anoxic volume as a viable alternative to improve nutrient removal under current operating conditions. Finally, the proposal seeks to strengthen treatment efficiency, ensure regulatory compliance, and ensure the operational sustainability of the WWTP in the face of future growth in flow and pollutant load.